Factors Associated with Systemic Lupus Erythematosus-Associated Interstitial Lung Disease and Clinical Outcomes: A Systematic Review and Meta-Analysis - Mislav Radić; Petra Šimac Prižmić; Tina Bečić; Hana Đogaš; Josipa Radić; Damir Fabijanić; Andrea Gelemanović; Dijana Perković (Medicina, 2026)
Background and Objectives: Interstitial lung disease (ILD) is an uncommon but clinically important manifestation of systemic lupus erythematosus (SLE). We aimed to identify factors associated with SLE–ILD, evaluate factors associated with clinical outcomes in established disease, and quantitatively synthesize comparable data. Materials and Methods: PubMed, Web of Science, Scopus, and the Cochrane Central Register of Controlled Trials were searched from inception through July 2026. English-language observational studies of adults with SLE reporting factors associated with ILD occurrence or outcomes in established SLE–ILD were eligible. Random-effects meta-analyses were conducted when at least three studies reported comparable data. Results: Eight observational studies were included. Across five studies, patients with SLE–ILD were older than those without ILD (mean difference 8.49 years, 95% confidence interval [CI] 5.52–11.46; p < 0.0001; I2 = 66.9%). Across three studies, SLE–ILD was associated with higher odds of Raynaud phenomenon (odds ratio, 3.01; 95% CI, 1.49–6.09; p = 0.0022; I2 = 28.8%). Other study-level associations included smoking, serositis, features of overlap connective tissue diseases, selected autoantibodies, and Krebs von den Lungen-6 (KL-6). In established SLE–ILD, baseline forced vital capacity and cohort-specific clinical and imaging features were associated with outcomes, while population-based cohorts linked ILD with increased mortality. Conclusions: Older age and Raynaud phenomenon were the factors most consistently associated with SLE–ILD across the available comparative studies. Because most included studies were observational, these findings should be interpreted as associations rather than evidence of causality. Prognostic evidence remains limited and heterogeneous.